A study of character as exemplified by two of our greatest presidents - Kimble, Venus (My University, 1908)
Introduction: A question that might interest the public of today is; Why Abraham Lincoln and Theodore Roosevelt are among the best liked of our presidents? The writer in trying to answer this question has found it necessary to compare and contrast the different periods of the life.
Citation: Kimble, Venus. A study of character as exemplified by two of our greatest presidents. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Abraham Lincoln; Theodore Roosevelt; Presidents; Politics; Graduating theses; Senior theses; Theses